Effect of Abiotic Conditions on Growth, Mycotoxin Production, and Gene Expression by Fusarium fujikuroi Species Complex Strains from Maize - Ting Dong; Shouning Qiao; Jianhong Xu; Jianrong Shi; Jianbo Qiu; Guizhen Ma (Toxins, 2023)
Fusarium fujikuroi species complex (FFSC) strains are a major concern for food quantity and quality due to their strong ability to synthesize mycotoxins. The effects of interacting conditions of water activity, temperature, and incubation time on the growth rate, toxin production, and expression level of biosynthetic genes were examined. High temperature and water availability increased fungal growth. Higher water activity was in favor of toxin accumulation. The maximum amounts of fusaric acid (FA) and fumonisin B1 (FB1) were usually observed at 20–25 °C. F. andiyazi could produce a higher content of moniliformin (MON) in the cool environment than F. fujikuroi. The expression profile of biosynthetic genes under environmental conditions varied wildly; it was suggested that these genes might be expressed in a strain-dependent manner. FB1 concentration was positively related to the expression of FUM1, while a similar correlation of FUB8 and FUB12 with FA production could be observed in F. andiyazi, F. fujikuroi, and F. subglutinans. This study provides useful information in the monitoring and prevention of such toxins entering the maize production chain.